A systematic review of factors related to parents' treatment decisions for their children with autism spectrum disorders. (April 2018) - Wilson, Meghan; Hamilton, David; Whelan, Thomas; Pilkington, Pamela
Highlights: Child behaviour, parent beliefs, and stress are related to ASD intervention use. Parents report a wide range of reasons for their intervention decisions. Understanding decision-making can inform ways to support parents with this process. Abstract: Background: There are many treatment options for children with Autism Spectrum Disorder (ASD). Misinformation and easy access to ineffective treatments complicates the decision-making process for parents. Research on implicit factors (e.g., parent or child characteristics) and declared factors (e.g., parent-reported reasons) contributes to an understanding of what influences these decisions. Method: The aim of this systematic review was to examine the significance of factors associated with treatment selection. The review was conducted in accordance with the PRISMA protocol. Results: The search revealed 51 studies which contained data on implicit and/or declared factors associated with treatment selection. The data were tabulated by factor and synthesised. The severity of a child's behavioural problems, parental stress, and parent beliefs about ASD were consistently identified as implicit factors associated with the use of particular treatments. A wide range of reasons for treatment choices were declared by parent respondents, including; the individual needs of their child, recommendations from others, practical reasons (e.g., cost), child age, hope for recovery, hope for improvement, and concerns about side-effects. Conclusion: A better understanding of these factors will inform targeted educational approaches which encourage evidence-based practice and a more informed view of treatments not yet supported by research.